Detection of Bacterial Biofilms in Chronic Pharyngitis Resistant to Medical Treatment. (July 2015) - Badran, Hatem; Salah, Mohamad; Fawzy, Mohamed; Sayed, Amal; Ghaith, Doaa
Objective: To evaluate the role played by adenoids as a reservoir for infection in children assigned for adenoidectomy. Methodology: The study included 35 children with adenoid hypertrophy. All patients underwent clinical examination and adenoidectomy, adenotonsillectomy, or myringotomy with insertion of aeration tube according to indications. Surgical specimens were processed for conventional bacterial culture examination and to assay for biofilm formation. The obtained adherence values using spectrophotometer at 595 nm (OD595) was used to classify isolates according to its biofilm forming capacity. Results: We did adenotonsillectomy and myringotomy with insertion of aeration tube in 5 patients having adenotonsillitis with otitis media with effusion. We did adenotonsillectomy in 12 patients having adenotonsillitis and adenoidectomy in 18 patients having adenoid hypertrophy. Thirty-one surgical specimens showed bacterial growth on conventional media, while 4 specimens failed to give growth. The predominant organism was H influenzae then Staph aureus and Strept pneumoniae . Thirty-two specimens showed biofilm forming capacity (BFC) of variable extent, while others showed no BFC. Conclusion: Adenoids act as a bacterial reservoir secondary to bacterial biofilm formation so could induce chronicity and initiate development of complications. Determination of BFC using the proposed protocol is feasible, inexpensive, and available and spares the need for sophisticated instruments or approaches.